ANALISIS STRATIFIKASI SOSIAL DALAM PEMBANGUNAN MASYARAKAT DI KENAGARIAN SITUJUAH GADANG - Yohanis (Jurnal Administrasi Publik dan Pemerintahan, 2022)
This research used the Qualitative Approach the informan of this research are niniak mamak of Kenagarian Situjuah Gadang, the social leader, the community who have social status in that village. The Supporting data has taken from the office of Wali Nagari, the stratification of the informant purposively. The data collected by observation, interview and documentation study. To know the vaildity of data the researches used triangulation technique and technique of analysis data by analysing qualitative data that begin from data reduction, presenting data and make the conclution. The result of this research an is follow: 1) the form of social stratification of the community, 2) The role of social stratification in the community development has been that changed in their community life in Kenagarian Situjuah Gadang. The change was backed up by leading, the need of the community and government in globalization era with various need and problem. Meanwhile the village in a concept of heritage tradition (traditional heritage) is a unit of social organization which was governed by penghulu group, that was barned from homogen farming community and simple, so they cannot able to face democracy and otonomy the community of Kenagarian Situjuah Gadang had been pismed with the stratification/koel that are : social stratification of culture, structure social stratification, social politic stratification. They have the mission and vision in the development of the whole community.